2020
DOI: 10.1002/adfm.201910633
|View full text |Cite
|
Sign up to set email alerts
|

All‐Fluorescence White Organic Light‐Emitting Diodes Exceeding 20% EQEs by Rational Manipulation of Singlet and Triplet Excitons

Abstract: White organic light-emitting diodes (WOLEDs) composed of conventional fluorophores possess color purity, low efficiency roll-off, and rare metal absence, but suffer from theoretical limits due to the lack of triplet utilization. Due to the different diffusion distance for singlets and triplets, multiple Förster resonance energy transfer (FRET) channels can be adequately built up. Herein, besides the complementary component, a blue fluorescence layer, hosted by pure hydrocarbon material SF4-TPE, is put forward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 41 publications
(35 reference statements)
1
14
0
Order By: Relevance
“…Notably, device W2 achieves outstanding EL efficiencies of η ext,max , η C,max , and η P,max values of 26.2%, 89.6 cd A −1 , and 100.5 lm W −1 , respectively, with a small efficiency roll-off of 12.9% at 1000 cd m −2 . To the best of our knowledge, device W2 is the most efficient all-fluorescence single-emitting layer white OLEDs reported so far (table S8) ( 6 , 50 – 55 ). These results further validate the success of our molecular design of robust and efficient luminescent materials for high-performance OLEDs.…”
Section: Resultsmentioning
confidence: 98%
“…Notably, device W2 achieves outstanding EL efficiencies of η ext,max , η C,max , and η P,max values of 26.2%, 89.6 cd A −1 , and 100.5 lm W −1 , respectively, with a small efficiency roll-off of 12.9% at 1000 cd m −2 . To the best of our knowledge, device W2 is the most efficient all-fluorescence single-emitting layer white OLEDs reported so far (table S8) ( 6 , 50 – 55 ). These results further validate the success of our molecular design of robust and efficient luminescent materials for high-performance OLEDs.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, η EQE roll-offs at 100 and 1000 cd m -2 were as low as 7% and 15%, respectively. Consequently, PhCzSPOTz supported its UTBL WOLEDs with the best comprehensive performance reported so far among HF WOLEDs, 51 which was also comparable to PH and TADF counterparts (Figure 2d). In comparison, η EQE values of DCzSPOTz-hosted UTBL WOLEDs were nearly halved to 11.8% for the maximum, and 10.4% and 8.8% at 100 and 1000 cd m -2…”
Section: Oled Performancementioning
confidence: 60%
“…[ 110 ] The manipulation of singlet and triplet excitons is also a popular strategy for generating white light in OLEDs. [ 111,112 ] In another study, an OLED based on a TADF molecule demonstrated a high maximum EQE of >29.3% and good stability ( T 90 ≈ 600 h for 1000 cd m −2 ). [ 113 ] Hence, it would be very interesting to examine how the triplet excitons in g‐CN may be harnessed in a similar way.…”
Section: Structure and Optical Properties Of G‐cnmentioning
confidence: 99%